Symposium 9: Researching Learning in Networked Learning – Phenomenography and Variation theory as empirical and theoretical approaches - Booth, Shirley (Proceedings of the International Conference on Networked Learning, 2008)
Phenomenography and variation theory are presented as empirical and theoretical approaches to research on learning, in particular as applicable to networked learning. Their epistemological, ontological and methodological underpinnings are described. Three studies of relevance are described briefly, and used as examples for a discussion of the research questions that can be asked in empirical studies, the approaches to data collection and/or data generation, and analysis, and the presentation of results in wider frameworks that widen research possibilities. The questions are variants of “What is the qualitative variation of ways in which people experience some phenomenon they meet in their everyday lives?”, in higher education, generally applied to students and their experience of aspects of their study and learning. Learning is seen at an individual level, but empirical results are at a collective level; individuals contribute only fragments of the data that is to be analysed as a whole pool, and results are presented at the collective level of the pool. This paper can be seen as a comparison, a contrast and, possibly, a complement to the other two papers in the symposium which present approaches which are related directly to learning at the individual level and the social level, respectively.